Thermal Analysis of MCM Packaging - Andonova, A. (Elektronika ir Elektrotechnika, 2014)
This paper describes the use of infra-red thermography for the thermal study in the development stage of custom enclosures for multi-chip modules. Some limitations of conventional thermographic measurements are discussed and an approach for enhancing its application to quality control and diagnostics of faulty multi-chip module packages is proposed. The results from thermal measurements of radio-frequency range multi-chip module prototype in an open and a closed Quad Flat No Lead package are presented. DOI: http://dx.doi.org/10.5755/j01.eee.20.5.7110